A Scoping Review of Islamic-Based Spiritual Nursing Care Methods in Critical Care Units - Junaidy Suparman Rustam; Waraporn Kongsuwan (Fakultas Keperawatan Universitas Andalas, 2026)
Addressing the spiritual needs of critically ill Muslim patients is crucial to prevent spiritual distress that may occur during their treatment. Tailored interventions aligned with their beliefs can significantly alleviate spiritual distress, but there is a lack of comprehensive research in this area. This review study aimed to identify existing literature on the methods tailored to address spiritual needs for Muslim patients with critical illness who are hospitalized in critical care units according to Islamic principles and practices. This scoping review is based on the PRISMA ScR (Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews) checklist. Five electronic databases were searched: COCHRANE, ProQuest, Scopus, CINAHL, and PubMed. The keywords are used for searching, including “Islamic-based intervention” AND “spiritual nursing care” AND “Muslim patients with critical illness”. The ten included articles were analysed and appraised following the protocol of The Joanna Briggs Institute. The results revealed that the selected studies employed various methodologies, including both qualitative and quantitative studies. The review synthesized detailed descriptions of Islamic-based spiritual nursing care in critical units and categorized them into five methods: 1) prayer facilitation, 2) environmental accommodation, 3) spiritual counselling, 4) respect for Islamic practices, and 5) use of Islamic phrases. The methods outlined for delivering Islamic-based interventions provide crucial guidance on how to address the religious and cultural requirements of Muslim patients during their challenging circumstances.